1994
DOI: 10.1136/adc.71.5.404
|View full text |Cite
|
Sign up to set email alerts
|

Delayed adolescent growth in homozygous sickle cell disease.

Abstract: Analysis of the growth abnormalities in sickle cell disease has been limited by the lack of longitudinal observations in individuals, and by an inability to quantitate the observed patterns. To investigate the timing and pattern of the adolescent growth spurt, longitudinal observations of height from the Jamaican cohort study were fitted to a mathematical model of growth (Preece-Baines model 1). The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
4
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 15 publications
5
38
4
3
Order By: Relevance
“…The findings of this study corroborate previous studies that reported lower stature than healthy controls in young and normal stature in adults with sickle-cell anaemia 7,15,16 . Other studies have however observed that children with sickle-cell anaemia did not reach normal height as adults 4,16,17 . The frequency and severity of injuries resulting from sickle-cell anaemia, as well as the interference of environmental issues, can impact negatively on growth.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The findings of this study corroborate previous studies that reported lower stature than healthy controls in young and normal stature in adults with sickle-cell anaemia 7,15,16 . Other studies have however observed that children with sickle-cell anaemia did not reach normal height as adults 4,16,17 . The frequency and severity of injuries resulting from sickle-cell anaemia, as well as the interference of environmental issues, can impact negatively on growth.…”
Section: Discussionsupporting
confidence: 83%
“…Most available data refers to cross-sectional observations 5,6 , except for studies from a Jamaican cohort that evaluated growth and puberty in individuals from birth to adulthood. Studies on the persistence of impaired stature and on possible repercussions of restricted growth and pubertal delay in adults with sickle-cell anaemia are controversial 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Growth may be another factor contributing to pulmonary abnormalities in children with SCD as seen by its impact on FEV1% of predicted trend [36][37][38][39][40]. Our data showed those with delayed GV not only experienced a faster rate of decline in FEV1% of predicted but also were unable to regain the normalcy of lung growth and lung function.…”
Section: Impact Of Medication Status Gv and Acsmentioning
confidence: 57%
“…Since publication of the CSSCD data, several other studies have revealed that children and adolescents with SCD had significantly lower height, weight, and BMI compared with reference growth curves. [9][10][11][12][13][14][15][16] In general the adverse influence of SCD has been more pronounced for weight than height. Endocrine dysfunction, poor nutrient intake, micronutrient deficiencies, hypermetabolism, and high protein turnover have been described in individuals with SCD and growth failure.…”
Section: Discussionmentioning
confidence: 99%